Deconstructing Barriers To Access Rapid Public Transportation For Commuters With Visual Impairment: A Study Of Embodied Experiences In Delhi Metro-Train (Journal of Namibian Studies : History Politics Culture, 2023)
An inclusive city seeks innovative ways to accommodate diverse interests and practices of people with different needs. It requires that the basic rights of freedom, equality, and condition of justice and dignity of all its citizens (including persons with disabilities) are ensured. Delhi is undoubtedly one of the most diverse urban city centers in India. The Delhi metro train with its many accessibility features seems an archetype of an ideal inclusive and open city for all. Nonetheless, such moves towards disabled-friendliness fail to neutralise all the imperfections in absolute terms. The initiatives oriented to hassle-free travelling could not adequately meet the diverse transport needs of regular commuters with sight disability and do not fully address gaps embedded in metro rail infrastructure. Not with standing these measures to foster seamless journey for the disabled passengers, visually impaired users still come across those barriers which may not be directly apparent in public but are certainly the product of their personally embodied experiences.In the wake of Delhi metro assertion for better mobility and accessible transit environment, the present paper pursues deconstructive approach and attempts to figure out the pragmatic challenges encountered by visually impaired commuters that are often left unnoticed. These covert experiential hindrances are normally manifested in the day to day journey of Delhi Metro train. This is an empirical study based on survey findings stemming from Delhi field survey conducted during PhD course (2016-18). It primarily thrives upon qualitative data pertaining to personal narratives of 40 visually impaired respondents belonging to metropolis of Delhi about their everyday perceptions of transit accessibility, while travelling in metro train.